Evaluation of the viability of old seeds of several important agricultural weeds - Šikuljak, Danijela; Uludag, Ahmet; Anđelković, Ana; Trkulja, Nenad; Božić, Dragana; Vrbničanin, Sava (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2024)
Persistent seed banks are equally important in agriculture and invasion biology. While seed vitality persistence exemplifies an eternal uphill battle for weed control in agriculture, it signals a potential invasiveness of species in invasion biology. Considering yield losses caused by Amaranthus retroflexus, Abutilon theophrasti, Chenopodium album and Datura stramonium in agriculture, and the importance of Ambrosia trifida as an emerging invader in Europe, the objective of this study was to test the viability and longevity of the aged seeds of these economically important weeds. Three seed viability/longevity tests were conducted: the crush test, germination test in Petri dishes, and 3,5-triphenyltetrazolium chloride (TTC) test.The results revealed a significant variation in germination potential among the tested species. The highest vitality was observed in 7-year-old seeds of A. retroflexus (41.67 %), followed by 16-year-old A. theophrasti seeds (17.78 %), 13-year-old C. album seeds (15.00 %) and 17-yearold D. stramonium seeds (7.5 %). Furthermore, a remarkable seed longevity was documented in the tested species (with the exception of A. trifida), preserving their germination potential for over half a century. Seed germination was recorded in 49-year-old seeds of D. stramonium, 53-year-old seeds of A. retroflexus, 58-year-old seeds of A. theophrasti and 59-year-old seeds of C. album, in strong evidence of the persistence of these weed species’ seeds in the environment.
Keywords: germination; seed longevity; seed persistence; viable seeds; weed seeds